Ketidaklengkapan Norma Batas Keabsahan Pengesampingan Pasal 1266 Kitab Undang-Undang Hukum Perdata: Normative Incompleteness Regarding the Validity Limits of the Article 1266 Waiver in the Indonesian Civil Code - Nur Aini, Putri Aisyah; Djumikasih; Ido Nurhayati, Prawatya (Faculty of Law, Universitas Brawijaya, 2026)
Article 1266 of the Indonesian Civil Code stipulates that the cancellation of a reciprocal agreement due to breach of contract must be requested through a court ruling. In practice, however, waiver clauses excluding this provision are frequently included in various agreements, allowing unilateral termination without judicial proceedings. The central issue examined in this study is the normative incompleteness within the Civil Code, which does not explicitly regulate the validity limits of such waiver clauses, thereby generating multiple interpretations and legal uncertainty. This research employs a normative juridical method and the approaches used in this study include a statutory approach, a conceptual approach, and a case approach. Furthermore, this research aims to interpret the provisions in Article 1266 of the Indonesian Civil Code and to formulate the validity limits of the Article 1266 waiver clause in order to protect the weaker party. The findings reveal that diverging outcomes among the Kepanjen District Court, the Surabaya High Court, and the Supreme Court in the same case stem not from factual differences, but from varying legal bases and reasoning methods applied by judges at each judicial level. The absence of clear normative boundaries compels judges to independently engage in legal discovery, resulting in inconsistent rulings. An examination of scholarly opinions further reveals disagreement on whether Article 1266 is. Most scholars consider it mandatory and non-derogable, while others regard waiver clauses as common and legitimate in commercial contracts. This study concludes that clearer regulation of the validity limits of waiver clauses under Article 1266 is necessary to ensure legal certainty for all contracting parties.